Certain Admissible Classes of Multivalent Functions. (15th September 2014) - Aouf, M. K.; Srivastava, H. M.; Seoudy, T. M.
Abstract : We investigate some applications of the differential subordination and the differential superordination of certain admissible classes of multivalent functions in the open unit diskU . Several differential sandwich-type results are also obtained.